Client and counsellor experiences of abbreviated trauma-focused cognitive behavioural therapy for South African adolescents. (September 2022) - Kaminer, Debra; Letsatsi, Thato; Stewart, Shannon; Skavenski, Stephanie; Simmons, Candice
Although South Africa has high rates of child and adolescent trauma exposure and associated mental health difficulties, there is a poor evidence base for trauma interventions with youth in this setting. In a resource-constrained context, there is a need for brief evidence-based trauma treatments. However, abbreviated interventions may reduce the acceptability and tolerability of treatment for clients and impact treatment delivery by providers. We developed an abbreviated eight-session version of trauma-focused cognitive behavioural therapy. Using a sequential mixed-methods design, we piloted this intervention with 10 adolescents and their caregivers to assess the acceptability and tolerability of the abbreviated trauma-focused cognitive behavioural therapy model for participants, the degree of counsellor fidelity to the abbreviated treatment manual and counsellor experiences of implementation. The treatment completion rate was 90% and post-traumatic stress disorder symptoms reduced over the course of treatment for all treatment completers. Although there was flexibility in timing and dosing of delivery, counsellor fidelity to treatment components and treatment length was high. Thematic analysis of interviews with participants and counsellors indicated that, within this abbreviated trauma treatment, the therapeutic alliance was able to provide a solid foundation for trauma processing, there was adequate time to practice coping skills and the compressed trauma processing component was difficult but tolerable. Counsellors indicated that a degree of flexibility within fidelity to the abbreviated treatment model enhanced their implementation of the treatment. The findings provide evidence to support a formal evaluation of the abbreviated trauma-focused cognitive behavioural therapy treatment protocol.